ICT in auditing: Impact of audit quality norms on interpersonal interactions - Slobodan Kacanski (European Financial and Accounting Journal, 2016)
Productivity incentives have lately been driving auditors to introduce and utilize various computer-based tools to assist their work. The aim of this study is to understand how and why productivity incentives may disturb interpersonal interaction and relations between auditors at different ranks, in the context of assurance service. A case study was carried out with auditors affiliated with Danish subsidiaries of Big 4 audit firms to inspect the implementation and utilization of global audit methodology (GAM), which is the ICT-based platform that guides subordinate auditors through the audit process. The results highlight that superior auditors tend to experience prevalent trust in ICT tool over subordinate auditors, where such conditions reduce the opportunity for experiencing comfort by subordinates, while superiors still perceive comfort due to being comfortable with procedures that are administered by the tool. Finally, this mechanism further creates conditions under which the necessity for establishing interactions and relations between auditors of different ranks become diminished.
Keywords: M42; 650; Audit quality; Global audit methodology; Information and communication technologies; Interactions